A decision support model for civil engineering projects based on multi-criteria and various data - Issa, Usama H.; Miky, Yehia H.; Abdel-Malak, Fam F. (Journal of Civil Engineering and Management, 2019)
This paper develops a model, introduced in software, namely Multi-Criteria Decision-Making Model (MCDMM). The model helps decision makers selecting the most suitable alternative based on the customer requirements and preferences. Analytic Hierarchy Process (AHP) and Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) form a package that covers most available data types in construction projects. In MCDMM, AHP produces criteria relative weights according to their influence on the discussed problem, while Fuzzy TOPSIS is applied to rank the available alternatives. The model consists of two modules, first one uses AHP only to deal with precise, qualitative alongside quantitative data, while the other module combines AHP with Fuzzy TOPSIS due to the importance of linguistic variables to cover undocumented data. MCDMM is verified using two real case studies. The model is applied to a real case project for constructing solar power plants at Saudi Arabia. A decision required to select the most suitable surveying technique for producing Digital Terrain Model (DTM) among four alternatives (Total Station, Remote Sensing, Photogrammetry, and Global Positioning Systems). This issue is studied and key points are identified for prioritizing among them. Total Station is selected based on the model results.